WEBVTT
00:00:03.090 --> 00:00:12.700
Write the equation of line that passes through the points two, negative two and negative two, 10 in the form ππ₯ plus ππ¦ plus π is equal to zero.
00:00:15.040 --> 00:00:21.380
So in this question, weβre asked to find the equation of a straight line given the coordinates of two points that lie on the line.
00:00:23.210 --> 00:00:26.340
Weβll answer this question using the slope-intercept method.
00:00:26.660 --> 00:00:36.650
First, weβll find the equation of the straight line in the form π¦ equals ππ₯ plus π, where π represents the slope of the line and π represents the π¦-intercept.
00:00:38.320 --> 00:00:45.070
This wonβt give the equation of the line in the specific form thatβs been asked for: ππ₯ plus ππ¦ plus π is equal to zero.
00:00:45.260 --> 00:00:47.760
So weβll need to do some rearrangement at the end.
00:00:49.550 --> 00:00:52.800
Letβs recall first how to calculate the slope of a line.
00:00:54.550 --> 00:01:07.850
The slope of the line joining the points with coordinates π₯ one, π¦ one and π₯ two, π¦ two is equal to the change in π¦ divided by the change in π₯: π¦ two minus π¦ one over π₯ two minus π₯ one.
00:01:09.730 --> 00:01:13.800
Now, letβs substitute the coordinates in this question into the formula for the slope.
00:01:15.460 --> 00:01:19.460
π¦ two minus π¦ one is equal to 10 minus negative two.
00:01:21.150 --> 00:01:25.080
π₯ two minus π₯ one is equal to negative two minus two.
00:01:26.850 --> 00:01:31.790
This simplifies to 12 over negative four which is equal to negative three.
00:01:33.640 --> 00:01:35.730
So the slope of the line is negative three.
00:01:36.190 --> 00:01:42.930
Substituting this value into our equation for the line gives π¦ is equal to negative three π₯ plus π.
00:01:44.620 --> 00:01:47.750
Next, we need to find the value of π β the π¦-intercept.
00:01:49.180 --> 00:01:56.880
To do this, we can use the fact that either of these two points lie on the straight line and, therefore, their coordinates satisfy the equation of the line.
00:01:58.510 --> 00:02:03.880
Using the first point, this means that when π₯ is equal to two, π¦ is equal to negative two.
00:02:04.090 --> 00:02:10.350
And so we can substitute this pair of values into the equation of the line to give an equation that we can solve for π.
00:02:12.150 --> 00:02:21.340
Substituting two for π₯ and negative two for π¦ gives the equation negative two is equal to negative three multiplied by two plus π.
00:02:21.990 --> 00:02:23.180
Now, we solve for π.
00:02:24.850 --> 00:02:27.510
Negative three multiplied by two is negative six.
00:02:27.610 --> 00:02:31.270
So we have negative two is equal to negative six plus π.
00:02:32.870 --> 00:02:36.270
To solve this equation, we need to add six to both sides.
00:02:37.730 --> 00:02:39.780
This gives four is equal to π.
00:02:41.420 --> 00:02:45.410
Now, we know the value of π, we can substitute this into the equation of our line.
00:02:46.720 --> 00:02:50.210
We have π¦ is equal to negative three π₯ plus four.
00:02:51.760 --> 00:03:00.100
Remember weβre asked for the equation of a straight line in the form ππ₯ plus ππ¦ plus π is equal to zero, so we need all of the terms on the same side.
00:03:00.520 --> 00:03:02.080
We could group them on either side.
00:03:02.280 --> 00:03:07.360
But if I grouped the terms on the left, then the coefficients of both π₯ and π¦ will be positive.
00:03:09.000 --> 00:03:17.750
In order to group the terms on the left-hand side of this equation, I need to add three π₯ to both sides and also subtract four from both sides.
00:03:19.420 --> 00:03:26.910
This gives the equation of the straight line in the requested format: three π₯ plus π¦ minus four is equal to zero.